(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
In the 1990s, there seemed to be a complementarity between the needs of the newly independent Central Asian states, and the political and economic interests of the European Union. Yet the EU failed to establish traction in the region and its ability to exert leverage has remained low. One problem is a dissonance in mutual perceptions, reflecting negative images. Thiscreates misunderstandings andresentments.The relationship between the EU and the Central Asian states must be re- calibrated to emphasise partnership not mentorship. Another problem is that EU projects are ambitious in scope but poorly resourced, and thus often fall short of expectations. A third problem is that the EU has been unable to establish itself as a unitary actor in the region. Bilateral links with individual EU member states are more effective. Unless the EU succeeds in overcoming its internal divisions it will be difficult to implement a coherent regional strategy.